Estrategias liberales y progreso urbano en Bogotá (1863-1886). - Montoya Pino, Ana Patricia (Revista: Módulo Arquitectura CUC)
The administrative, economic and political reforms of the radical liberals in the second half of the 19th century in Colombia resulted in an ideal of urban progress in the city of Bogotá. These republican principles materialized in a series of urban symbols with clear objectives of political representation, citizen construction and communication with the world, which determined ways of thinking and building the city. Although Bogotá did not undergo an evident physical transformation during the 19th century, it is possible to identify, in the last decades, the intentions of its administration regarding the ideals of urban progress framed in the value of the public and the construction of the nation. In this sense, the question that this paper seeks to answer is: How did Colombian political thought and liberal administrative strategies of the second half of the 19th century determine an image of progress in Bogotá? Its answer is based on the review of primary sources such as press and publications of the time, in addition to Municipal Agreements between 1863 and 1886.